Cross-Border Trade, Industrial Integration, and Regional Connectivity: Inner Mongolia’s Contribution to China’s Dual Circulation Strategy (Journal of Interdisciplinary Insights, 2025)
This study examines the role of Inner Mongolia in advancing China’s dual circulation strategy through cross-border trade, industrial integration, and regional connectivity. Drawing on policy documents, trade statistics, and case-based analysis, the research highlights how Inner Mongolia functions as a geostrategic hub within the China–Mongolia–Russia Economic Corridor and a critical node in the Belt and Road Initiative. The findings demonstrate that Inner Mongolia’s border advantages, resource endowments, and infrastructural investments enable it to support domestic circulation through industrial upgrading and supply chain resilience, while simultaneously contributing to international circulation via diversified export channels and logistics corridors. The study also explores institutional arrangements, including bonded zones, free trade mechanisms, and cooperative frameworks with Mongolia and Russia, which strengthen the region’s integrative capacity. However, challenges such as environmental constraints, resource dependence, and policy coordination gaps persist. The research underscores Inner Mongolia’s evolving role as both a frontier of national security and a bridge of international cooperation, offering insights into how border regions can shape China’s reconfigured global economic geography.
Keywords: Dual Circulation Strategy; Cross-Border Trade; Industrial Integration; Regional Connectivity; Belt and Road Initiative